Estimation of road cut slope stability along the national and state highway of Garhwal Himalaya (India) applying slope mass rating and kinematic analysis - Biswajit Bera; Soumik Saha (Results in Earth Sciences)
Slope stability assessment of different road cut slopes has been conducted along the National Highway in Garhwal Himalaya, Uttarakhand (NH-34, NH-134, NH-7, NH-107 and a state highway from Dharasu to Tilwara). Slope instability issues in the Himalayan terrain are radically increasing due to high anthropogenic activities and rapid growth of urban centers since past years. Road networks in mountainous areas are the main source of transportation and socio-economic development. In this concerned study, forty (40) road cut slopes have been selected. These sites are selected based on lithology and structure. Diverse slope stability quantification methods along with various modes of failures have been systematically analyzed. The entire region falls under the tectonically active belt or the vicinity of the active fault zones that make the slopes inherently unstable. The Geological Strength Index (GSI) and Rock Mass Rating (RMR) have been applied for determination of slope conditions. Slope mass stability has been evaluated using Slope Mass Rating (SMR) index. The RMR rating ranges from 26 to 87 and the SMR values of forty (40) roads cut slopes range from 10 to 91. The kinematic analysis shows that most of the probable slopes failures are susceptible under planar and wedge failure. This study will definitely help to reduce the loss of life and property and also helps the ongoing constructional processes along the road section.